ANALISISI BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP INTENSITAS KERJA DAN KONTRIBUSI PENDAPATAN ASISTEN RUMAH TANGGA - Krisnaryana, I Made; Yasa, I Gusti Wayan Murjana (PIRAMIDA, 2018)
Respondents in this study are married women who work as a household assistant. Objects in the study include age, wages, education, the number of dependents, work intensity and income contribution. The sample in this study amounted to 96 respondents. In this research the method used to collect information and data that is observation, interview and depth interview. Data analysis technique used is path analysis / path analysis and test sobel to analyze indirect influence through intervening variable. The result of the research shows that age, wage, and dependent have direct and significant influence to work intensity, and age, wage, dependent amount and amount of husband’s income have a direct and significant effect to income contribution, and age, wage, and dependent influence indirectly Through work intensity variables on income contribution of married women who work as household assistants